Fetal hydrops as ultrasound congenital toxoplasmosis sign - Lacunza-Paredes, Rommel Omar (2014)
This case reports a rare ultrasonographic  sign of congenital toxoplasmosis, fetal hydrops, as the only manifestation of fetal compromise. Definitive diagnosis was done in the newborn who presented hepatosplenomegaly, chorioretinitis and absence of cerebral calcifications, being both mother and newborn positive for toxoplasmosis serology.